Entrepreneurial Spirit of Vegetable Vendors at Kliwon Market: A Competence Paradox Analysis - Gentur Ageng Sejati; Dumasari Dumasari; Sulistyani Budiningsih; Watemin Watemin (PT FORMOSA CENDEKIA GLOBAL, 2026)
The agricultural sector remains a critical pillar of Indonesia's micro-economy. This study exhaustively analyzes the entrepreneurial spirit among Micro, Small, and Medium Enterprises (MSMEs), specifically vegetable vendors at Kliwon Market, Karanglewas. Furthermore, it identifies structural and psychological obstacles to business development. Employing a descriptive quantitative method, 75 respondents were selected via Cluster and Convenience Sampling. Findings reveal a